Intuitu fidelis servittii sui. : diplomatics and literacy, gender and politics in the medieval Low Countries : Thérèse De Hemptinne : selected essays - De Paermentier, Els, 1975-; Van Tricht, Filip (Gent : Academia Press, 2013)
In October 2012, Thérèse de Hemptinne retired after a successful academic career at the department of (medieval) History at Ghent University. Carrying on and strengthening the internationally recognized Ghent tradition of Auxiliary Sciences for the study of the Middle Ages, Thérèse de Hemptinne taught for many years the Bachelor's and Master's courses of Diplomatics and Palaeography. Following her research interests, which from the 1990s onward gradually expanded to focus on the position and role of women in a medieval man's world, Thérèse de Hemptinne also integrated gender as a methodological tool of analysis into the Master's courses 'Historical Criticism' and the 'Gender Research Seminar', and acted as a supervisor of many Master's theses produced in the field of women and gender studies. The critical edition of the charters of the counts of Flanders Thierry and Philip of Alsace (1128-1191) can be considered one of the most important scholarly achievements of Thérèse de Hemptinne.
Keywords: Hemptine, Thérèse de, -- 1946-.